2012
DOI: 10.1002/biof.1043
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of the fermentation properties and potential prebiotic activity of caprine cheese whey oligosaccharides in batch culture systems

Abstract: The prebiotic effect of oligosaccharides recovered and purified from caprine whey, was evaluated by in vitro fermentation under anaerobic conditions using batch cultures at 37°C with human faeces. Effects on key gut bacterial groups were monitored over 24 h by fluorescence in situ hybridization (FISH), which was used to determine a quantitative prebiotic index score. Production of short-chain fatty acids (SCFAs) as fermentation end products was analyzed by high-performance liquid chromatography (HPLC). Growth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The ability of B. infantis ATCC 15697 to use multiple specific carbohydrate structures (2′FL, LNT, 3′SL, 6′SL, DSL, LNH, Sialic Acid, LSTc, LNnT and LNnH) within the pool was also Previous studies have demonstrated statistically significant increases in Bifidobacterium and Bacteroides growth following incubation with GMO [12]. Similarly, GMO has also been shown to increase levels of bifidobacteria using in vitro fermentation models and in in vivo mouse trials [15,39].…”
Section: Prebiotic Effects Of Gmomentioning
confidence: 95%
“…The ability of B. infantis ATCC 15697 to use multiple specific carbohydrate structures (2′FL, LNT, 3′SL, 6′SL, DSL, LNH, Sialic Acid, LSTc, LNnT and LNnH) within the pool was also Previous studies have demonstrated statistically significant increases in Bifidobacterium and Bacteroides growth following incubation with GMO [12]. Similarly, GMO has also been shown to increase levels of bifidobacteria using in vitro fermentation models and in in vivo mouse trials [15,39].…”
Section: Prebiotic Effects Of Gmomentioning
confidence: 95%
“…Recovery of OSs from caprine milk is an expensive option, whereas it would be more economical to extract them from a by‐product such as cheese whey, as most of the lactose and OSs are transferred into the whey (Oliveira et al . ). Numerous papers and patents deal with OSs in whey, but they mostly refer to specific galactooligosaccharides (GOSs) obtained from lactose by enzymic reaction (transgalactosylation) and do not refer to the natural milk OSs, produced in the lactating mammary gland of domestic species (Oliveira et al .…”
Section: Animal Milk Os As Alternative Sources For Hmomentioning
confidence: 97%
“…Also, recent research work points out to the potential of caprine milk as a source of bioactive compounds, namely for naturally extracted OSs from caprine milk whey and its utilisation as prebiotics (Oliveira et al . ,b) and lactoferrin (Parc et al . ).…”
Section: Future Opportunities With Animal Milks: Whey As Raw Materialsmentioning
confidence: 99%
“…We have previously shown that a caprine oligosaccharideenriched fraction (CMOF) supported the growth of selected bifidobacterial strains isolated from breast-fed infants, and stimulated in vitro production of acetate and lactate [16]. Oliveira et al (2012) [17] has also demonstrated the prebiotic activity of CMOF in a batch culture system inoculated with adult human feces. The aim of this study was to determine the effects of prenatal consumption of CMOF on the colon microbiota and milk composition of the dams, and the offspring's development.…”
Section: Wwwmnf-journalcommentioning
confidence: 99%
“…Oliveira et al. (2012) has also demonstrated the prebiotic activity of CMOF in a batch culture system inoculated with adult human feces. The aim of this study was to determine the effects of prenatal consumption of CMOF on the colon microbiota and milk composition of the dams, and the offspring's development.…”
Section: Introductionmentioning
confidence: 99%